Investigating the effect of using Multi-Level Yielding Pipe Damper dampers in steel structures under earthquake force in the horizontal direction (Journal of Civil Engineering Researchers, 2023)
Multi-level Pipe Damper (MPD) recently proposed by the authors is a passive control device to reduce the seismic vibration. In this research, seismic response of steel structures equipped with MPD is studied. To evaluate the effects of the proposed damper, typical 8 story steel buildings are modeled and their seismic responses under three earthquake excitations are investigated using dynamic nonlinear time-history analyses by ETABS program. Results show the effectiveness of MPD to altering the seismic response of the structures. Moreover, using MPD decreases the structural and nonstructural damages noticeably by limiting the inter story drifts because of the secondary hardening branch of force-displacement respectively proving the effectiveness of the proposed damper as a retrofitting technique for structures at high seismic risk areas.
Keywords: Multi-level pipe damper; Passive Control of Structure; seismic vibration; dynamic analysis; structural control